Management strategies of burns associated hyperthermia: A case report - Jonathan Bayuo (Elsevier, 2017)
Introduction: Hyperthermia in the burn injured patient has been noted to exist either in the presence or absence of infection. However, there is a need to manage this feature aggressively as if left unmanaged; it might lead to other deleterious effects. Objective: Thus, this case report assesses the management strategies instituted in the management of burns associated hyperthermia. Case report: A thirty-four year old male who sustained thermal burns was admitted with a baseline temperature of 36.1 °C. However elevated temperature to the level of 40.40 °C was noted but other tests proved the absence of infection. Several strategies were instituted to resolve the hyperthermic state. Conclusion: It was noted that these strategies possess limited efficacy and there is need to assess other modalities that works best and cost effective. Further research is also warranted in understanding the nature of hyperthermia in the absence of infection in the burned patient. Keywords: Burns, Hyperthermia, Management strategies